Integrated seismic ambient noise, magnetotellurics and gravity data for the 2D interpretation of the Vallès basin structure in the geothermal system of La Garriga-Samalús (NE Spain). (June 2021) - Mitjanas, G.; Ledo, J.; Macau, A.; Alías, G.; Queralt, P.; Bellmunt, F.; Rivero, Ll.; Gabàs, A.; Marcuello, A.; Benjumea, B.; Martí, A.; Figueras, S.
Highlights: The multi-physics characterization of the geothermal system has allowed the creation of a new conceptual model. The Vallès Fault Zone has been set as the reservoir and the main path for the thermal fluids. Our geophysical results show a new geometry for the Miocene basin. The combination of different geophysical methods has proved to be a good option to corroborate our new interpretation. Abstract: The integration of geophysical methods, together with the previous information of the Vallès basin area, has resulted in the creation of a new conceptual model that explains La Garriga-Samalús geothermal system. The integration of complementary geophysical methods seems to be a good option for the preliminary stages of a geothermal system exploration, especially in urban areas. An integrated seismic ambient noise, magnetotellurics, and gravity methods were used to determine the geological units and structures which control the La Garriga-Samalús geothermal system. The 2D resistivity and density models have allowed the identification of the four main units which regulate the geothermal system: the Miocene basin, the Prelitoral Range unit, the Vallès Faut Zone, and the Paleozoic basement. The interpretation of our models set the Vallès Fault Zone, which is characterized by an anomalous low resistivity and low density, as the main path for the hot fluids. Moreover, the geophysical characterization established a new geometry for the Miocene basin. The Miocene basin presents a stepwise morphology, with the minor thickness towards the fault and an increasing thickness towards the center of the basin. This geometry seems to be related to synthetic normal faults. These results have evidenced that, although, in some geothermal systems, the warm water may create an insufficient physical contrast; the appropriate use of some techniques can still be useful for the exploration of medium and low-temperature geothermal systems.